Interlukine-17 Polymorphism in Patients with Inflammatory Bowel Disease ( IBD ) in Al-Anbar Province - Thikra Majid Muhammed AL-Obaidy; Hasan Ali Mutar; Thaer Abdul Qader Saleh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Tetra amplification refractory mutation system polymerase chain reaction technique (tetra ARMS PCR)ARMS-PCR method was used to genotyping of IL-17A and IL-17F , The impact of IL-17A and IL-17Fgenotypes on the production of interleukins in IBD patients and control groups were determined andInterleukins gene polymorphisms role in IBD infection. significant deference at (p ? 0.05 ) for each rs763780in IL-17 F in patients especially Genotype TT,TC,CC were 31 (51.67%),19 (31.67%),10 (16.67%) \ andrs2275913 in IL-17 A in patients especially Genotype GG,GA,AA were 18 (30%),23 (38.33%),19 (31.67%).As well as genotyping of rs763780 in IL-17 F showed significant increase at a significant level of P?0.05in both TC and CC genotypes in the cases samples compared with the control samples. the odds ratio was2.8894 and 22.3333 for TC and CC genotypes respectively at confidence interval up to 7.8 and 397 forboth genotypes. T allele are more frequent in both cases and control and it have odds ratio as 5.021 Andgenotyping of rs2275913 in IL-17 A showed significant increase at a significant level of P?0.01 for the AAgenotyping in the cases samples compared with the control samples, while the GA genotyping did not showany significant differences, ), the odds ratio for GA genotypes was 2.3590 at confidence interval up to 5.8,while it was 8.4444 at confidence interval up to 32.9 for AA genotypes. G allele are more frequent in bothcases and control and it have odds ratio as 3.319 at confidence interval up to 6